Study on suitability and spatial distribution of human settlement environment in arid areas based on GIS and analytic hierarchy process - Geng, Manguo; Liu, Benteng; Zhang, Wei (Frontiers in Ecology and Evolution, 2023)
Scientific evaluation of the suitability of human settlement in arid areas and a grasp of their spatial differentiation characteristics are of great significance for the implementation of regional human settlement environment (HSE) improvement according to local conditions. In this study, we took Gansu Province (GS), a typical arid area in China, as the research object. First, based on field research, we used the analytic hierarchy process to determine the weights of 12 evaluation indicators and build an HSE evaluation model from the two dimensions of nature and humanities. Then, we conduct a comprehensive evaluation of each factor based on the GIS spatial analysis module. Finally, we used the GIS natural breakpoint method and zoning statistics to understand the suitability of the HSE and its spatial distribution characteristics in GS Province. The study findings can be summarized as follows:(1) The spatial distribution of the suitability of the natural environment in GS Province shows that the east-central part of the province is significantly higher than the northwestern, and there is a big difference between localities. (2) The comprehensive suitability of human settlement in GS Province appears as a spatial distribution characteristic, gradually decreasing from the central urban area to the surrounding areas. The suitability index of the living environment is between 0.26 and 0.71. (3) The area sizes of the five types of suitability are ranked as the following: low suitable (138,502 km² ) > moderately suitable (133,761 km² ) > critical suitable (97,244 km² ) > high suitable (47,459 km² ) > unsuitable (38,980 km² ); in 14 cities, the average value of habitat suitability index is more than 0.5 accounting for 42.9%. Our research not only fills a gap in the research of human settlement in arid zones but also provides policy support for government departments to improve human settlement.